2013
DOI: 10.1172/jci65268
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes increases mortality after myocardial infarction by oxidizing CaMKII

Abstract: Diabetes increases oxidant stress and doubles the risk of dying after myocardial infarction, but the mechanisms underlying increased mortality are unknown. Mice with streptozotocin-induced diabetes developed profound heart rate slowing and doubled mortality compared with controls after myocardial infarction. Oxidized Ca 2+ /calmodulin-dependent protein kinase II (ox-CaMKII) was significantly increased in pacemaker tissues from diabetic patients compared with that in nondiabetic patients after myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
222
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(240 citation statements)
references
References 72 publications
(108 reference statements)
9
222
0
7
Order By: Relevance
“…Computer code was written in C++ and compiled using Intel Composer XE 2011 for Linux. Computer simulations were performed on a Dell PowerEdge R515 server (dual 6 core, 32 GB RAM running CentOS 6.2), as described 21, 22, 27, 28, 29, 30. Regression was performed using MATLAB R2014b (MathWorks) on a MacBook Pro with a 2.5‐GHz Intel Core i7 processor (Apple Inc).…”
Section: Methodsmentioning
confidence: 99%
“…Computer code was written in C++ and compiled using Intel Composer XE 2011 for Linux. Computer simulations were performed on a Dell PowerEdge R515 server (dual 6 core, 32 GB RAM running CentOS 6.2), as described 21, 22, 27, 28, 29, 30. Regression was performed using MATLAB R2014b (MathWorks) on a MacBook Pro with a 2.5‐GHz Intel Core i7 processor (Apple Inc).…”
Section: Methodsmentioning
confidence: 99%
“…At the molecular level, SERCA2a is glycosylated by AGEs formation in the STZ T1DM rat model and was proposed to be a contributory factor conspiring towards depressed pump activity (Bidasee, et al, 2004;Brownlee, 1995). As discussed in Section 3.0 CaMKII is a regulator of RyR2 function and thus it is significant that oxidised CaMKII (ox-CaMKII) has been detected in human pacemaker tissue from diabetic patients after an MI, a finding mirrored in nodal tissue in an STZ T1DM model (Luo, et al, 2013). However, the effect of CaMKII oxidation in the context of RyR2 function was not been explored.…”
Section: Chronic Hyperglycaemia Leads To Protein Post-translational Mmentioning
confidence: 98%
“…It has recently been suggested that activation of a mitochondrial/ox-CaMKII pathway contributes to increased sudden death in diabetic patients after myocardial infarction (Luo et al, 2013). CaMKII pathway has been implicated in diabetic retinopathy development, diabetic vascular dysfunction and renal dysfunction in a model of insulin-dependent diabetes (Benter et al, 2005;Kato et al, 2008;Kim et al, 2010).…”
Section: Discussionmentioning
confidence: 99%